Implementasi Konsep â€œHomie Holisticâ€ pada Redesain Interior Gereja Kristen Kalam Kudus Jayapura - Aguita, Moonica; Sitindjak, Ronald Hasudungan Irianto; Frans, Stephanie Melinda (Intra, 2019)
Churches are religious buildings for Christians which provides spiritual activities for itspeople. The word church comes from a Portuguese word â€œigrejaâ€ which means herd of sheep.This term in Greek is Ekklesia, which means called out.Other than to worship God, churches have an important role to increase the relationsbetween people through the presence of the communal room. One of the church that is in Jayapura is Kalam Kudus Catholic Church which is located at a main avenue in Jayapura city, with the capacity to accommodate many people which makes this church one of the biggest church in Jayapura city.